Efektivitas Penggunaan Aplikasi Quizizz dalam Model Pembelajaran Langsung (Direct Instruction) terhadap Hasil Belajar Peserta Didik Kelas XI MIPA 1 SMAN 11 Takalar Tahun Pelajaran 2021/2022 (Materi Pokok Laju Reaksi) - syahriani syahriani; Muhammad Anwar; Muhammad Fudhail Majid (Jurusan Kimia FMIPA UNM, 2022)
This research is a descriptive study that aims to describe the effectiveness of the Quizizz application on the direct instruction model to improve student learning outcomes in class XI MIPA 1 SMA Negeri 11 Takalar on the subject matter of reaction rate. The Subject of this research is class XI MIPA 1 which consists of 20 students. The data obtained using the instrument of student learning outcomes. The results of the descriptive analysis obtained the average value before treatment was 23 and after treatment was 80,9. And the average value of N-Gain is 0,76 in the high category. Based on the results of the study, it can be concluded that the Quizizz application in the direct instruction model is in the high category for improving student learning outcomes in class XI MIPA 1 SMAN 11 Takalar on the subject of reaction rates. Keywords: Quizizz application, direct instruction, learning outcomes, reaction rate.